2017
DOI: 10.1038/ncomms14478
|View full text |Cite|
|
Sign up to set email alerts
|

Arylmethylamino steroids as antiparasitic agents

Abstract: In search of antiparasitic agents, we here identify arylmethylamino steroids as potent compounds and characterize more than 60 derivatives. The lead compound 1o is fast acting and highly active against intraerythrocytic stages of chloroquine-sensitive and resistant Plasmodium falciparum parasites (IC50 1–5 nM) as well as against gametocytes. In P. berghei-infected mice, oral administration of 1o drastically reduces parasitaemia and cures the animals. Furthermore, 1o efficiently blocks parasite transmission fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 45 publications
1
51
0
4
Order By: Relevance
“…C) Chemical structures of the most potent BACADs . D) Chemical structures of AASs 33 – 35 with antischistosomal activity …”
Section: Anthelmintic Drug Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…C) Chemical structures of the most potent BACADs . D) Chemical structures of AASs 33 – 35 with antischistosomal activity …”
Section: Anthelmintic Drug Therapymentioning
confidence: 99%
“…In addition, studies with adult S. mansoni confirmed that AASs exert fatal effects on morphology, physiology, and survival of female and male worms in vitro. This was achieved using concentrations similar to PZQ ( 9 ) …”
Section: Anthelmintic Drug Therapymentioning
confidence: 99%
See 3 more Smart Citations